2020
DOI: 10.24843/mtk.2020.v09.i04.p311
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Penalaran Proporsional Pada Siswa Kesulitan Belajar Matematika Di Sekolah Inklusif

Abstract: Many Mathematical concepts require students to use proportional reasoning. Proportional reasoning can be an indication of the level of students' mastery of mathematics on subjects involving comparison problems. Problems solving with proportional reasoning can be even more challenging for students with mathematic learning disabilities. The purpose of this study was to analyze the reasoning of students of difficulty learning mathematics in inclusive schools. Research approach with qualitative methods. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…The activities performed by female students are in line with Norton's (2005) statement that using multiplication and division operations to solve problems involving proportional situations does not necessarily develop a deeper understanding of proportional reasoning (Yuwono & Putri, 2020). This is reinforced by the statement (Park et al, 2010) which states that "an area identified as a problem type for which students not having learned a formal proportional expression cannot understand the multiplicative relationship very well".…”
Section: S: Yessupporting
confidence: 58%
See 4 more Smart Citations
“…The activities performed by female students are in line with Norton's (2005) statement that using multiplication and division operations to solve problems involving proportional situations does not necessarily develop a deeper understanding of proportional reasoning (Yuwono & Putri, 2020). This is reinforced by the statement (Park et al, 2010) which states that "an area identified as a problem type for which students not having learned a formal proportional expression cannot understand the multiplicative relationship very well".…”
Section: S: Yessupporting
confidence: 58%
“…Fatmaningrum states that students'reasoning abilities are different from one another, but their abilities to solve math problems are very important and can be done through various ways of solving (Yuwono & Putri, 2020). Reasoning is a basic skill in mathematics and is needed to achieve several objectives, for example, to understand mathematical concepts, to use more flexible mathematical ideas and procedures and to reconstruct previously understood knowledge but it is forgotten (Ball & Bass, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations